2006
DOI: 10.1614/ws-05-167r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of relative time of emergence on nitrogen responses of corn and velvetleaf

Abstract: Nitrogen (N) management markedly affects weed competition with crops. The effect of N availability on plant competition varies with a plant's abilities to capture and use N. Accordingly, we expected the N effect on plant competition to change with the relative emergence time of competing individuals. This hypothesis was tested by growing corn and velvetleaf plants in target and neighbor roles and comparing their N responses. Sowing times were varied, so that target plant emergent dates were constant, whereas n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…One explanation for greater response of sweet corn to Vetch IR :RyeVetch IR ratio and soil inorganic N %IR compared with weeds is that sweet corn more rapidly acquired early mineralized N released from vetch. Corn is a relatively large-seeded crop with a high relative growth rate that allows corn plants to rapidly establish their root systems and scavenge soil resources (Harbur and Owen 2006). In comparison, most weed species are small-seeded (Seibert and Pearce 1993), and despite having a high relative growth rate, their small seed size puts them at a considerable initial disadvantage because of lower energy reserves to devote toward root proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…One explanation for greater response of sweet corn to Vetch IR :RyeVetch IR ratio and soil inorganic N %IR compared with weeds is that sweet corn more rapidly acquired early mineralized N released from vetch. Corn is a relatively large-seeded crop with a high relative growth rate that allows corn plants to rapidly establish their root systems and scavenge soil resources (Harbur and Owen 2006). In comparison, most weed species are small-seeded (Seibert and Pearce 1993), and despite having a high relative growth rate, their small seed size puts them at a considerable initial disadvantage because of lower energy reserves to devote toward root proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Delayed POST application can lead to weed competition early in the growth cycle of corn. Alternatively, the lack of residual activity of glyphosate leads to the presence of weeds later in the season Harbur and Owen 2006;. Many studies have shown that the emergence and density of weeds are critical factors in determining the level of competition.…”
Section: Introductionmentioning
confidence: 99%